The Impact of CYP2C19 Loss-of-Function Polymorphisms, Clinical, and Demographic Variables on Platelet Response to Clopidogrel Evaluated Using Impedance Aggregometry. (April 2017) - Mărginean, Alina; Bănescu, Claudia; Moldovan, Valeriu; Scridon, Alina; Mărginean, Mihai; Bălaşa, Rodica; Maier, Smaranda; Ţăruşi, Mariana; Dobreanu, Minodora
Introduction: Clopidogrel is an antiplatelet drug widely used in patients with acute coronary syndromes or stroke. Despite adequate antiplatelet therapy, some patients develop acute ischemic events. This is partly attributed to the fact that they have poor inhibition of platelet reactivity, despite treatment. This study aimed to assess the impact of clinical and demographic variables and of cytochrome P450 2C19 (CYP2C19) loss-of-function polymorphisms on platelet response to clopidogrel evaluated using impedance aggregometry in an East European population. Methods: The study included 189 clopidogrel-treated patients with acute coronary syndromes and noncardiogenic ischemic stroke. Platelet aggregation was evaluated by impedance aggregometry. CYP2C19 loss-of-function polymorphisms were detected using the polymerase chain reaction restriction fragment length polymorphism technique. Various clinical and demographic data were also recorded. Results: In our data set, 81% of the patients were responders and 19% nonresponders to clopidogrel therapy. The distribution of CYP2C19 polymorphisms was as follows: 61.1% of patients were CYP2C19 wild-type homozygotes, 27.7% of patients were CYP2C19*2 heterozygotes, 1.1% of patients were CYP2C19*3 heterozygotes, and 10% of patients were CYP2C19*2 homozygotes. The highest level of association with clopidogrel response status was found for CYP2C19 polymorphisms, concomitant aspirin treatment, leukocyte and platelet count, history of myocardial infarction, arterial hypertension, and ward where patients were admitted. Conclusion: The prevalence of clopidogrel resistance in our East European population was in line with that reported for Western populations. Clopidogrel response was significantly influenced by the presence of CYP2C19 polymorphisms. Interestingly, the concomitant use of aspirin had a significant impact on platelet response to clopidogrel, indicating a synergic interaction between these drugs.